Innovative Hydrogel Design: Tailoring Immunomodulation for Optimal Chronic Wound Recovery - Chun‐Mei Lai; Wei‐Ji Chen; Yuan Qin; Di Xu; Yue‐Kun Lai; Shao‐Hua He (Advanced Science)
Abstract Despite significant progress in tissue engineering, the full regeneration of chronic wounds persists as a major challenge, with the immune response to tissue damage being a key determinant of the healing process's quality and duration. Post‐injury, a crucial aspect is the transition of macrophages from a pro‐inflammatory state to an anti‐inflammatory. Thus, this alteration in macrophage polarization presents an enticing avenue within the realm of regenerative medicine. Recent advancements have entailed the integration of a myriad of cellular and molecular signals into hydrogel‐based constructs, enabling the fine‐tuning of immune cell activities during different phases. This discussion explores modern insights into immune cell roles in skin regeneration, underscoring the key role of immune modulation in amplifying the overall efficacy of wounds. Moreover, a comprehensive review is presented on the latest sophisticated technologies employed in the design of immunomodulatory hydrogels to regulate macrophage polarization. Furthermore, the deliberate design of hydrogels to deliver targeted immune stimulation through manipulation of chemistry and cell integration is also emphasized. Moreover, an overview is provided regarding the influence of hydrogel properties on immune traits and tissue regeneration process. Conclusively, the accent is on forthcoming pathways directed toward modulating immune responses in the milieu of chronic healing.